Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: • The Effectiveness of Using Gamification Strategy in Enhancing the Motivation of Business Administration Students to Learn the Principles of Financial Management Course in Saudi Arabia Dr. Razaz Houssien Felimban • The Strategic Rivalry Between Turkey and Iran and Its Implications for the Middle East Mr. Ali Khidr Matar • The modern management accounting methods and their relationship to achieving the competitive advantage of business organizations A field study of the industrial sector in Hafar Al-Batin(2020-2025) Co-Prof. Noureldaim Eltayeb Yousif Elhag • The Russia–Ukraine War and the Struggle to Shape the New International Order Mr. Kamal Kamel Tarhini • Subcontracting: A Study in the Framework of Administrative Contracts Under the Saudi System Mr. Abdulrahman Abdulaziz Ibrahim Al-Mohana • Corporate Governance Practices and Their Contribution to Achieving Saudi Arabia’s Vision 2030 Objectives: An Applied Study on Emerging Cybersecurity Companies Mr. Mohammad Abdulaziz Alduriweesh • The impact of using the balanced scorecard on the organization’s strategic planning (An applied study on the Ministry of Social Development) Prof. Sulaiman Hussein Al-Muzain, Mr. Muhammad Ishaq Al-Salti • Credit Risk Analysis and Its Impact on Financial Performance Indicators Based on Accounting Profit: An Applied Study on Saudi Stock Exchange Institutions During the period 2018 – 2022 Co-Prof. Alsadig Mohamed Salim